Jak go słyszą? Studenci o reportażu radiowym. Uwagi o instytucji słuchacza - Klimczak, Kinga (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2008)
This article refers what students — young audience — think about radio document: what s exactly?, is it a kind of art or not?, what’s the most important in radio document? etc. Their opinions are confronted with scientists’ views.